Health system strengthening using a Maximizing Engagement for Readiness and Impact (MERI) Approach: A community case study - Teddy Kyomuhangi; Kimberly Manalili; Jerome Kabakyenga; Jerome Kabakyenga; Eleanor Turyakira; Eleanor Turyakira; Dismas Matovelo; Sobia Khan; Clare Kyokushaba; Heather MacIntosh; Jennifer L. Brenner; Jennifer L. Brenner; et al. (Frontiers Media S.A., 2022)
IntroductionHealth system strengthening initiatives in low and middle-income countries are commonly hampered by limited implementation readiness. The Maximizing Engagement for Readiness and Impact (MERI) Approach uses a system "readiness" theory of change to address implementation obstacles. MERI is documented based on field experiences, incorporating best practices, and lessons learned from two decades of maternal, newborn, and child health (MNCH) programming in East Africa.ContextThe MERI Approach is informed by four sequential and progressively larger MNCH interventions in Uganda and Tanzania. Intervention evaluations incorporating qualitative and quantitative data sources assessed health and process outcomes. Implementer, technical leader, stakeholder, and policymaker reflections on sequential experiences have enabled MERI Approach adaptation and documentation, using an implementation lens and an implementation science readiness theory of change.Key programmatic elementsThe MERI Approach comprises three core components. MERIChange Strategies (meetings, equipping, training, mentoring) describe key activity types that build general and intervention-specific capacity to maximize and sustain intervention effectiveness. The SOPETAR ProcessModel (Scan, Orient, Plan, Equip, Train, Act, Reflect) is a series of purposeful steps that, in sequence, drive each implementation level (district, health facility, community). A MERIMotivational Framework identifies foundational factors (self-reliance, collective-action, embeddedness, comprehensiveness, transparency) that motivate participants and enhance intervention adoption. Components aim to enhance implementer and system readiness while engaging broad stakeholders in capacity building activities toward health outcome goals. Activities align with government policy and programming and are embedded within existing district, health facility, and community structures.DiscussionThis case study demonstrates feasibility of the MERI Approach to support district wide MNCH programming in two low-income countries, supportive of health outcome and health system improvements. The MERI Approach has potential to engage districts, health facilities, and communities toward sustainable health outcomes, addressing intervention implementation gaps for current and emerging health needs within and beyond East Africa.